Emergency management on campus: Are we leaving the students behind?. Issue 7 (18th October 2018) - Ruddell, Rick; Patten, Ryan; Thomas, Matthew O.; Allen, Andrea; Hoard, Season
Abstract : The odds of a natural disaster or human‐caused hazard requiring a facility shutdown or evacuation are relatively low for any institution of higher education. However, campus security and university police departments across North America respond to serious incidents every day. For example, in August 2017, hundreds of students were trapped by flooding at the University of Houston, and in March 2018, Central Michigan University was locked down as an active shooter was on campus.